UTILISATION OF AUGMENTED REALITY FOR GENERATING ACTIVE LEARNING IN ARCHITECTURAL EDUCATION - Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Abd. Razak, Mohd Raziff; Asif, Nayeem; Yusof, Zeenat Begam; Azmin, Aida Kesuma; Ismail, Mohd. Norizhar (Journal of Architecture, Planning and Construction Management, 2025)
The advancement of Augmented Reality (AR) has impacted the world of architecture and has facilitated the construction industry to leap ahead, giving practitioners the ability to virtually visualize and spatialize design works with integration into the physical environment. Nevertheless, the utilization of the available visualization techniques in AR has not been widely used in the teaching and learning of architecture. Hence, this article aims to describe the exploration of utilizing AR in architectural education, as a method for generating active learning among students. This article also depicts case studies of the integration of AR visualization with architectural education by experimenting with techniques of AR application in the teaching and learning of building construction courses. Two (2) experimental projects were conducted with the substance of exploratory action research. The projects were carried out to experiment with the integration techniques and to assess the integration as attributes for successful learning. The two projects used a qualitative approach to have the exploratory inquiry of the experimentation, focusing on exploration of AR utilizations in two (2) building construction courses using steel and timber materials. This research shows that AR had been successfully utilized as the medium to disseminate architectural construction knowledge of both steel and timber construction materials. The experimentations also have inspired students to participate in the learning process actively and improved their cognitive learning capability.